SWOT analysis in the formulation of tourism development strategies for destinations - Goranczewski, Bolesław; Puciato, Daniel (Turyzm/Tourism, 2011)
The aim of the paper is to identify the role of SWOT analysis in the formulation of tourism development strategies for destinations. SWOT analysis helps to establish a reliable diagnosis of the internal potential shown by a tourism destination and its environment. In the Polish economic situation, SWOT analysis is frequently used in a fragmentary manner which should be considered as a serious methodological oversight and may jeopardize the value of the entire process related to the strategic management of the tourism destination.